Experimental reduction in blood oxygen-carrying capacity alters foraging behaviour in a colonial waterbird - Minias, Piotr; Kamiński, Maciej; Janiszewski, Tomasz; Indykiewicz, Piotr; Kowalski, Jarosław; Jakubas, Dariusz (Journal of experimental biology, 2023)
Oxidative metabolism is a key component of organismal physiology and it is primarily determined by aerobic capacity, which depends on the capacity of blood to carry oxygen. However, experimental manipulations of blood oxygen-carrying capacity are rarely implemented to test ecophysiological hypotheses in vertebrate populations. Here, we combined an experimental manipulation of blood oxygen-carrying capacity with GPS tracking to test whether suboptimal (reduced) haematological performance affects foraging behaviour in a colonial waterbird, the black-headed gull, Chroicocephalus ridibundus. First, a validation of phenylhydrazine (PHZ) treatment in gulls revealed a 9–18% reduction in haematocrit and blood haemoglobin concentration (via oxidative denaturation and haemolysis of erythrocytes). Then, GPS tracking of experimental (PHZ-treated) and control (saline-treated) gulls during the incubation period provided no support for reduced or suspended engagement in energetically costly activities (long-distance foraging trips) by experimental birds. Instead, we found evidence for fine-scale alterations in foraging behaviour of PHZ-treated individuals, which resulted in fewer foraging trips per unit time, but trips that were longer in duration and distance compared with those of control birds. This suggests reduced foraging performance of experimental birds (e.g. lower capacity to find and collect food during trips) or evasion of social competition, although no differences in the total investment in foraging may also suggest compensatory physiological responses to haemolytic anaemia. Our study contributes to a better understanding of the physio-ecological nexus in non-diving colonial avian species. Whether behavioural effects of reduced aerobic capacity have any implications for gull condition and reproductive performance should be the subject of further investigation.